DESIGN OF A SMART GATEWAY BASED ON REST API FOR DATA TRANSMISSION SYSTEM BETWEEN EDGE DEVICES AND SERVER IN THE AQUACULTURE SECTOR - Naura Azzahra, Iftitah
This research aims to design and implement a smart network gateway based on REST API to improve the efficiency and security of data transmission in the aquaculture sector. The background of this research is based on the need for aquaculture farmers to monitor environmental conditions in real-time and take preventive actions based on accurate and up-to-date data. The use of Internet of Things (IoT) technology in the aquaculture sector has provided various benefits, including the ability to monitor aquaculture environmental conditions such as water quality, temperature, and other important parameters. However, the main challenge faced is how to transmit this data efficiently and securely. Therefore, this research develops a system that combines data compression features using GZIP and ZLIB libraries and data encryption with the AES algorithm to ensure that the data sent is secure and efficient. The main objective of this research is to test the successful implementation of compression and encryption algorithms in reducing data size and transmission duration, as well as enhancing security during the data transmission process. Additionally, this research aims to evaluate the system's performance in real-world scenarios in the aquaculture sector. The research methods used include system testing in various data transmission scenarios between edge devices and servers, as well as comparative analysis of data size and transmission duration with and without compression and encryption. The testing is conducted using a dataset relevant to aquaculture environmental conditions, where the data is sent through the smart network gateway to the server for analysis and storage. The research results show that using the ZLIB library is more efficient in compressing data compared to GZIP, resulting in smaller data sizes and faster transmission durations. The testing indicates that the ZLIB + AES combination produces the most efficient compressed and encrypted data size compared to other combinations. Meanwhile, the AES + GZIP and AES + ZLIB combinations show increased data sizes and longer transmission durations due to the encryption process being done before compression, making the data more random and harder to compress effectively. This highlights the importance of the order of applying compression and encryption in data transmission systems. Furthermore, the designed system also shows the ability to integrate with existing IoT infrastructure, providing flexibility for aquaculture farmers to monitor their